A new application of oily cold rolling mill sludge for preparing Fe2O3/graphene as anodes for lithium-ion batteries1. Issue 71 (2nd August 2015) - Liu, Cheng; Wang, Xinjing; Ma, Peng; Chen, Jilu; Jiang, Jianzhong; Ai, Yani; Wang, Erqin; Han, Sheng; Rong, Shaofeng
<x xml:space="preserve">Abstract</x> A new application of oily cold rolling mill sludge for preparing Fe2O3/graphene as anodes for lithium-ion batteries.